Strategi peningkatan efisiensi pemungutan PPh Pasal 22: Pada transaksi perdangan internasional - Royani, Nindy Dwi; Rokhmah, Miftakhul; Ashfahany, Muhammad Nu’man; Maulida, Lutfia Uswatul (Maliki Interdisciplinary Journal, 2024)
PPh 22 is one of the many types of taxes in Indonesia. Import activities occur when the purchase of goods by domestic taxpayers to sellers abroad. The purpose of this research is to improve the tax collection process, optimize the results and improve the efficiency of Income Tax Article 22 collection. The approach used is a type of qualitative approach with the data obtained in the form of secondary data. The results obtained indicate that the strategies needed to improve the efficiency of PPh 22 collection are good collaboration between taxpayers and tax collectors; the need for a good tax management strategy; and also an income tax rate policy that can be accepted by taxpayers in order to increase the amount of tax received on ITA 22 on imports.